State space approach in assessing the existene of calendar Effects at international stock markets: its implication on efficient market hypothesis. - Arsad, Zainudin (Universiti Sains Malaysia, 2012)
This research investigates the existence and persistence of a few types of calendar effects in ten International stock markets covering the period from 1995 to 2010. Most previous studies have used the standard OLS and ARLMA-GARCH-type models, restricting the coefficients representing the mean returns for the calendar effects as constants over the sample or sub-sample periods.